1994
DOI: 10.1177/036354659402200608
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Remaining Patellar Tendon Width with Quadriceps Strength After Autogenous Bone-patellar tendon-bone Anterior Cruciate Ligament Reconstruction

Abstract: One hundred twenty-one patients were prospectively studied to determine whether the different remaining patellar tendon widths after central 10-mm bone-patellar tendon-bone graft harvest influenced the rate and level of quadriceps strength achieved during rehabilitation. Size of the patellar tendon width, measured at the same location in each patient, ranged from 24 to 35 mm. For this study, patients were grouped according to their remaining tendon size into small (14 to 17 mm; mean, 15.8), medium (18 to 20 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…25 However, by six months post-operatively, patellar tendon width no longer influences isokinetic quadriceps strength. 26 Future studies may benefit from incorporation of patellar tendon CSA to clarify the relation between patellar tendon width and quadriceps strength.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, by six months post-operatively, patellar tendon width no longer influences isokinetic quadriceps strength. 26 Future studies may benefit from incorporation of patellar tendon CSA to clarify the relation between patellar tendon width and quadriceps strength.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the characteristics of the donor site of the patellar tendon as seen on MRI after removal of the graft (Berg 1992;Coupens et al 1992;Koblik and Freeman 1993;Kamps et al 1994;Shelbourne et al 1994;Cerullo et al 1995;Nixon et al 1995). Although many MRI studies have shown gradual maturation of the donor site of the patellar tendon there is no information on the appearance at its insertion after removal of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…The bone-patellar-tendon-bone (BPTB) autograft is commonly used for reconstruction of the anterior cruciate ligament (ACL), but problems with the patella have been reported subsequently (Bose and Chong 1976;Bonamo, Krinick and Sporn 1984;Paulos et al 1987;Huegel and Indelicato 1988;Lambert and Cunningham 1988;Sachs et al 1989;Christen and Jakob 1992;Kleipool, Van Loon and Marti 1994;Rubinstein et al 1994;Tria, Alicea and Cody 1994). Histological and imaging studies of the donor site after graft harvesting have shown evidence of progressive healing (Berg 1992;Coupens et al 1992;Koblik and Free-man 1993;Kamps et al 1994;Karns et al 1994;Rubinstein et al 1994;Shelbourne et al 1994;Adriani et al 1995;Cerullo et al 1995;Nixon et al 1995). The structural integrity of the healed donor site, however, may be compromised at the tendon itself and also at its site of insertion into bone.…”
mentioning
confidence: 99%
“…Harvesting one-third of the patellar tendon could compromise the extensor mechanism of the knee, but the tendon probably has the capacity to regenerate to some extent [11,25]. The strength of the quadriceps muscle is reduced after the operation for a period of time [32], but one-third of the patellar tendon may be harvested without compromising ultimate quadriceps strength recovery [23,35]. Chronic instability after an ACL injury has been shown to be associated with hypotrophy of the quadriceps muscle [16].…”
Section: Discussionmentioning
confidence: 99%